(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Online shopping is a recent phenomenon in the world of Commerce and it will be the gateway for shopping in the world in near future. Due to increasing internet and mobile penetration, growing acceptability of online payments has provided the unique opportunity to the companies to connect with their customers. Business has been coming up with creative way to promote their product via online. At the same time, the customer satisfaction is crucial for success of any business as it directly impacts customer retention, brand reputation, and overall profitability. Satisfied customers are more likely to return for repeat purchases, recommend the business to others and contribute to a positive brand image. Hence the researcher has chosen the topic titled customers satisfaction towards online shopping. The study involves both primary and secondary data. The primary data collected through interview schedule from 100 customers who are shopping through online and the collected data analysed with the help of statistical tools such as percentage analysis, Garrett ranking and weighted average method to arrive the meaningful conclusion.